Asymptotic behavior of eigenvalues of hydrogen atom equation - Panakhov, Etibar S.; Ulusoy, Ismail (Springer International Publishing Ag, 2015)
We consider a spectral problem for a class of singular Sturm-Liouville operators on the unit interval with explicit singularity 2/x-2/x(2), related to the Schrodinger operator with radially symmetric potential. In particular, we give the asymptotic behavior of the eigenvalues of the hydrogen atom equation.
Keywords: hydrogen atom equation; analytic solutions; method of successive approximations